Hubungan Tingkat Pengetahuan Kosmetika dengan Perilaku Menghindari Kosmetika yang Mengandung Rhodamin-B - Karuniawaty, Aldes; Ambarwati, Neneng Siti Silfi (Universitas Negeri Jakarta, 2021)
Cosmetics is a necessity that has long been used and developed by humans. Along with the development of the era of increasing use of cosmetics, female students as consumers who use cosmetic products should have good knowledge about cosmetics. Cosmetics on the market are very diverse in terms of brands, types, uses, as well as colors and shapes. This study aims to determine the relationship between knowledge and behavior to avoid Cosmetics containing Rhodamine-B. This study uses a descriptive research method with a correlational approach and the sample of this research is the Make-up Education Students, Class of 2018 with total 30 students using random sampling. The data used is primary data and collected through a questionnaire. The analytical requirements test used in this study is the Kolmogorov-Smirnov Normality Test which shows a probability value (Sig.) of 0.080 for the cosmetic knowledge variable (X) and 0.198 for the behavioral variable to avoid cosmetics containing Rhodamine-B (Y). obtained > 0.05 significant level, so that both variables can be declared normally distributed. Hypothesis testing in this study uses the product moment correlation coefficient test and the significance test of the correlation coefficient. The results show r arithmetic of 0.625, which means it is greater than r table of 0.361, which means Ho is rejected and Ha is accepted. The correlation value of 0.625 indicates a strong correlation, this refers to the Correlation Coefficient Level. It can be concluded that there is a positive relationship between knowledge of cosmetics and behavior to avoid cosmetics containing Rhodamine-B.